Impaired Immune Responses and Antigen-Specific Memory CD4(+) T Cells in Hemodialysis Patients - Litjens, Nicolle Helena Renier (American Society of Nephrology, 2008)
Serologic responses to T cell–dependent vaccinations are severely attenuated in patients with ESRD, but the reasons for this is unknown. In this study, a detailed analysis of antigen-specific T cell responses was performed. Patients on hemodialysis and age- and gender-matched healthy control subjects were vaccinated with hepatitis B surface antigen (HBsAg), antigen-specific CD4(+) T cells were monitored at regular intervals with intracellular cytokine staining and proliferation assays. IL-2–and IFN-γ–producing CD4(+) T cells were identified as either central or effector memory CD4(+) T cells using antibodies directed against CD45RO and the chemokine receptor CCR7. Control subjects mounted a memory T cell response comprising both central and effector memory CD4(+) T cells, with the central memory response occurring 1 wk before the effector memory response. IL-2(+) HBsAg-specific memory CD4(+) T cells were primarily detected within the effector population. Patients with ESRD showed a delayed response of IL-2–and IFN-γ–producing central memory CD4(+) T cells, but their maximal responses were similar to those of control subjects. In contrast, patients with ESRD produced only 6.3% of the IL-2(+) HBsAg-specific effector memory CD4(+) T cells produced by control subjects (0.5 ± 0.2 × 10(4)/L versus 8 ± 3.5 × 10(4)/L; P < 0.001), and this impaired response correlated with antigen-specific T cell proliferation and anti-HBsAg IgG titers. In conclusion, the production of antigen-specific effector memory CD4(+) T cells after vaccination, which is critical to achieve an adequate humoral response, is severely impaired in patients with ESRD.